(Chemical Handling of Tapioca Waste Water) - Djubaedah, Endah; N.k, Mochamad Noerdin; Harjanto, Sri (Warta Industri Hasil Pertanian, 1994)
Chemical handling of tapioca waste water using coagulans (Alum and poly ammonium chloride), flocculan (polymer code 161),and areation had been done. The treatment in laboratory scale descreased BOD value from 148.59 mg/1 to 54.315 mg/1;COD value from 251.540 mg/1 to 138.875 mg/1; suspended solid from 31.8 mg/1 to 1.719 mg/1; and soluble solid from 2.87 mg/1 to 0.01 mg/1.these result were in accord with the local standard for waste water.